Chiral Thinking and Asymmetries of Writing Between Science and Literature: Primo Levi and Italo Calvino (Ticontre. Teoria Testo Traduzione, 2017)
This essay examines Levi’s La chiave a stella (1978) in relation to Calvino’s Palomar (1983) and in the context of a period of fertile questioning of the scientific/non-scientific distinction and hierarchy, represented by two significant volumes – I livelli di realtà a cura di M. P. Palmarini, Feltrinelli, 1984, and La sfida della complessità a cura di G. Bocchi e M. Ceruti, Feltrinelli, 1985. Both Levi and Calvino, as is well-documented, aspired to an «immaginazione scientifica-poetica» that might configure a «mappa del mondo e dello scibile, lo scrivere mosso da una spinta conoscitiva» (Calvino, Due interviste su scienza e letteratura). Interpreting both La chiave a stella and Palomar as experimental laboratory-like structures, I study transcribing activities as asymmetries of writing that connect the physical world to the hands of the writer or to recording instruments of the laboratory. With particular reference to La chiave a stella, I show how Levi’s exploration of asymmetry offers opportunities for substantive dialogue between literary and scientific research.